Atlantic crescent: building geographies of Black and Muslim liberation in the African diaspora - Morgan, Alaina M. (The University of North Carolina Press, 2025)
"In the period between the twentieth century's two world wars, Black and Muslim people from the United States, South Asia, and the Caribbean collided across an expansive diasporic geography. As these people and their ideas came into contact, they reignited the practice of Islam among people of African descent living in the United States and the Anglophone Caribbean and prompted them to adopt new understandings of their place in the world. As the freedom dreams of these diasporic communities met the realities and limitations of colonialism and race in the Atlantic world, Islam presented new strategies for combatting oppression and introduced new allies in the struggle. Envisioning the geography and significance of this encounter within what she calls the Atlantic Crescent, Alaina M. Morgan draws on an expansive archive to show how Black and Muslim people imagined, understood, and acted on their religious and racial identities. Morgan reveals how her subjects' overlapping diasporic encounters with Islam led to varied local adaptation as well as common ground to pursue liberation from racial subjugation and white supremacy"--